Uji Aktivitas Antibakteri Ekstrak Etanol Kulit Pohon Faloak (Sterculia sp.) Terhadap Bakteri Staphylococcus Aureus - Priska Ernestina Tenda; Maria Yangsye Lenggu; Marini Sriyuni Ngale (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Faloak is a medicinal plant that grows in extreme conditions in the East Nusa Tenggara region. Faloak has benefits for herbal treatment wherein the content of saponin compounds, steroids and triterpenoids, flavonoids, and alkaloids found in the bark of the faloak tree serves for the treatment of various diseases caused by bacteria. The purpose of this research is to know the antibacterial activity of ethanol extract of faloak bark (Sterculia sp.) On the growth of Staphylococcus aureus bacteria. Determination of antibacterial activity by a diffusion method using a cylinder, and see the existence of a clear zone around a cylinder. The results showed that the concentration of 22.5% w / v; 45% w / v; 75% w / v and 100% w / v were able to inhibit the growth of Staphylococcus aureus bacteria with mean inhibitory zone diameter of 1.33 cm, 1.66 cm, 1.90 cm, 2.13 cm, the concentration of the inhibitory zone is greater so that the effective concentration inhibiting the growth of Staphylococcus aureus bacteria is 100% w / v.